Embracing diversity under isolation and cease-fire: a poststructuralist look at administrators' policy on multilingualism - Mavioglu, Metin (Springernature, 2024)
Although multilingualism in higher education context continues to garner increasing scholarly interest, research remains scarce on school administrators' policies on multilingualism. To the best of our knowledge, this study constitutes one of the very few attempts to tackle this issue in higher education context and the first of its kind to pursue such endeavour in North Cyprus setting. This study seeks to investigate, through a post-structuralist perspective, the perceptions and policies of multilingualism by the director and assistant directors of an English preparatory school in a North Cyprus university which has flourished as a haven for international education. The study combines a multiplicity of data through semi-structured interviews and informal chats to provide a richer insight into the multifaceted case being investigated. The findings demonstrate that administrators regard multilingualism as a seal of internationalism and educational quality. They remain hesitant and even mostly sceptical, however, about whether translingual practice could offer any meaningful contribution to language learning processes. Although poststructuralist understanding considers truth and identity to be decentred and forever changing, and despite the scope of our study being limited to one particular institution only, our findings promise great potential for inspiring reflection and research in other universities in North Cyprus and elsewhere, which similarly aspire to international competition in higher education.
Keywords: English